The emergence of modern Hinduism: religion on the margins of colonialism - Weiss, Richard S. (University of California Press, 2019)
Introduction : rethinking religious change in nineteenth-century South Asia -- Giving to the poor : Ramalinga's transformation of Hindu charity -- The publication of Tiruvarutpa : the authority of canon and print -- Ramalinga's devotional poems: creating a hagiography -- The polemics of conflicting modernities -- The modernity of yoga powers in colonial India.